Urgensi Kepemimpinan Partisipatif di Sekolah - Silvi Titasari (CV Edujavare Publishing, 2024)
This study aims to determine the urgency of participatory leadership in schools. This study used a qualitative approach with data analysis. Through the analysis and interpretation of data from various scientific journals and books related to the urgency of participatory leadership in schools, the research findings revealed the urgency of participatory leadership in schools, including: creating a positive work climate, fostering two-way communication, providing motivation, fostering collaboration, and making informed decisions. In conclusion, participatory leadership fosters two-way communication and motivation, thus creating a conducive work climate. A conducive work climate fosters positive collaboration between the principal, teachers, and school staff.